KONSERVASI PENGETAHUAN LOKAL TANAMAN OBAT (EMPON-EMPON) DI HUTAN RAKYAT PERBUKITAN MENOREH KULON PROGO D.I YOGYAKARTA - , Irma Yeny ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Menoreh is a home for Javanese ethnics in Kulon Progo who has been using traditional medication plant which called empon-empon in their traditional health care system for thousand years. The knowledge has been transmitted orally to generations, but has been eroded in the last decades because of rapid cultural change. The study aimed to: 1) find and recognize the meaning, definition, characteristic, value and norm of empon-empon